2020
DOI: 10.1590/s1413-65382620000100010
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diagnosis as a Strategy for Implementing Inclusive Education in Poland1

Abstract: ABSTRACT: The 25th anniversary of the Salamanca Statement is a good opportunity to summarize to what extent the challenges described in it have been implemented by the signatory countries, all of which are members of UNESCO. This article presents a balance of achievements in implementing inclusive education in Poland, as well as a catalog of challenges for the future. Although the commitments to provide inclusive education for children and young people with special educational needs (SEN) arise from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Greater independence can be also associated with students’ greater intrinsic motivation [ 14 ]. It might have a huge impact on the effectiveness of the learning process [ 27 ]. Such an approach could be promoted by reducing chaos and exaggerated demands in every case of instability and disruption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater independence can be also associated with students’ greater intrinsic motivation [ 14 ]. It might have a huge impact on the effectiveness of the learning process [ 27 ]. Such an approach could be promoted by reducing chaos and exaggerated demands in every case of instability and disruption.…”
Section: Discussionmentioning
confidence: 99%
“…The research reports have showed that inclusive education could be effective for all learners thanks to the social, emotional and educational benefits of activities that involve students with different needs, preferences and personal resources [ 25 ]. These goals have been served by the introduction of solutions based on universal design learning (UDL), rational adjustments of curricula and lesson scenarios and selection and application of appropriate textbooks and training materials for the teaching–learning process [ 26 , 27 ]. If the implemented principles of UDL do not remove the barriers that prevent some students from accessing the learning process, it is necessary to introduce rational adjustments and modifications in the following areas: equipment, lighting, timetables, methods, forms, teaching content, didactic aids and methods of school assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Opisane powyżej sytuacje należy oczywiście analizować w szerszym kontekście -ograniczonej wiedzy dotyczącej możliwości rozwojowych osób z niepełnosprawnościami i chorobami przewlekłymi oraz braku edukacyjnych placówek integracyjnych (które mogły być tworzone w Polsce dopiero po roku 1991, por. Bogucka, 1996;Domagała-Zyśk, Knopik, 2020). Konsekwencją jednak takiego segregacyjnego modelu leczenia i rehabilitacji był utrudniony kontakt rodziny z ich chorym czy niepełnosprawnym członkiem, co często owocowało zaburzeniami czy nawet zerwaniem wzajemnej relacji.…”
unclassified